‘We refugees’: (Un)othering in visual narratives on displacement - Smyczyńska, Katarzyna (Nordic Journal of English Studies, 2018)
This article focuses on four contemporary visual narratives which deal with the theme of (literal or metaphorical) refuge, and its difficult circumstances and consequences. The books under discussion have been chosen for their specific visual poetics, which acquires a significant narrative function in each story. The narratives’ portrayals of displacement are evocative for at least two reasons. First, they make metaphorical links between the past and the present, appealing to cultural memory and reworking it in various ways. Second, they communicate their ethical message relying on the affective potential of the material qualities of the medium—the book, and on the emotional impact of embodied memory evoked by visual means.